2005
DOI: 10.1016/j.jtcvs.2005.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Single–suture line placement of a pericardial stentless valve

Abstract: Objective: Implantation of bioprostheses in the supra-annular position with the single suture line was first applied by O'Brien to porcine stentless valves. The aim of this study was to evaluate the clinical performance of the Pericarbon Freedom stentless bioprosthesis (Sorin Biomedica Cardio, Saluggia, Italy) implanted in supra-annular position with the single-suture line technique. The single-suture approach for the Pericarbon Freedom stentless bioprosthesis is obtained by trimming away all the extra tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 12 publications
2
34
1
1
Order By: Relevance
“…Current result for LVEF was contradicted by some other researches. Their researches showed the improvement in LVEF after FS valve replacement (21,20). Although our study demonstrated reduction in LVEF, the mean LVEF was still in normal range.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Current result for LVEF was contradicted by some other researches. Their researches showed the improvement in LVEF after FS valve replacement (21,20). Although our study demonstrated reduction in LVEF, the mean LVEF was still in normal range.…”
Section: Discussioncontrasting
confidence: 46%
“…The AVA was improved from 0.78 ± 0.35 cm2 preoperatively to 1.90 ± 0.56 cm2 at 1 month and 1.89 ± 0.56 cm2 at 12 months. (21) Based on current observation, the result of LVEF demonstrated a reduction from 65.75 ± 6.30 % to 61.25 ± 11.84 % within 5 months postoperatively. Current result for LVEF was contradicted by some other researches.…”
Section: Discussionmentioning
confidence: 57%
“…The design modification that resulted in the FS was aimed at allowing subcoronary, supra-annular implantation with only one suture line, achieved through the trimming of all extra tissue from the PF valve inflow side, and the scalloping of the outflow side to preserve the valve assembly suture. 20 As such, the FS combines the latest-generation bovine pericardial tissue and novel anticalcification treatment, with the singlesuture, subcoronary implantation technique first applied by O'Brien to porcine stentless valves. 21 This design allows imitation of the native healthy valve through unrestricted adaption to each individual patient's anatomy.…”
Section: Evolution Of the Fs Stentless Valvementioning
confidence: 99%
“…Care must be taken to avoid any laceration of the valve leaflets with a needle tip and also to prevent any damage of the assembly suture of the valve. Some surgeons have suggested to start suturing at the right coronary sinus, followed by the left coronary sinus, and finally the NC sinus, 20 but in fact, any order can be followed 25 ( Figure 2F). There is large individual variability in root anatomy, and the NC sinus often presents wider and deeper than the symmetric prosthesis.…”
mentioning
confidence: 99%
“…К альтернативным методам лечения относятся протезирование аорталь-ного клапана биологическими протезами бескаркасной конструкции. Более требовательная к хирургической технике имплантация с одной стороны и приводящая в результате к лучшим гемодинамическим характеристи-кам с другой стороны, операция с применением бескар-касных биологических протезов становится вариантом выбора при хирургическом лечении сенильных аорталь-ных пороков сердца [10][11][12][13].…”
unclassified